ANALISIS HUBUNGAN MOTIVASI GURU TERHADAP MINAT BACA SISWA SEKOLAH DASAR DI INDONESIA - Aisah Wahdini Manik; Ananda, Kasih; Siregar, Rhaudatul Ilmi; Octananda, Salta; Bancin, Suci Lestari; Juliati, Juliati (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to determine the relationship between teacher motivation and student reading interest at the elementary school level. Low student reading interest remains a challenge in education, characterized by a lack of enthusiasm and independent reading habits. This study uses a descriptive qualitative method. A literature review from various scientific journal sources was conducted. The results of the study indicate that teacher motivation plays a significant role in increasing students' interest in reading. Teachers who act as facilitators, motivators, and mentors are able to create a learning environment that supports a culture of literacy. The strategies implemented include providing reading corners, counseling on the importance of reading, and conducting literacy activities 15 minutes before class. These findings reinforce the importance of the active role of teachers in fostering reading interest through a fun and sustainable approach.